Daya Juang Pasangan Dispensasi Nikah - Sari, Adibah Putri Malika; , Dr. Eny Purwandari, M.Si; , Dra. Hj. Chusniatun, M.Ag (2017)
The purpose of this research is to discover how patterns of adversity quotient couples having marital dispensation. Researchers used a qualitative approach with three key informants and three informants supporters. Key informants were the perpetrators of the dispensation of marriage, while supporters informants are a couple of key informants. In this study, the researcher used interview as a data collector. Couple dispensation marriage should lose one of the most important tasks in the juvenile stage is to prepare the marriage and household. Teens who get married at an early age have a new role in life is to be an adult. It will be cause many problems to be faced by the marriage dispensation pasangang. With the problems that must be faced by the couples marriage dispensation actors require adversity quotient to deal with any problems that there are in the household. Results from this study showed that the problems faced by couples marriage dispensation diverse, such as the economic problems that are not well off, childish attitude of self informant respectively, a third person, even a family treatment of domestic violence. With the problems that occur informant must have adversity quotient to be accomplishing and find solutions in each of these challenges so that they coached households could be maintained. adversity quotient has four aspects: control, origin/ ownership, reach and endurance. Each pair has a different control, no control is low and those that are high, as well as in the aspect of the origin / ownwership. Most informants have a high reach and the endurance aspect of itself throughout the informant has a high durability.